Simultaneous Detection and Differentiation of Highly Virulent and Classical Chinese-Type Isolation of PRRSV by Real-Time RT-PCR - Shuqi Xiao; Yaosheng Chen; Liangliang Wang; Jintao Gao; Delin Mo; Zuyong He; Xiaohong Liu (Journal of Immunology Research)
Porcine reproductive and respiratory syndrome (PRRS) is a leading disease in pig industry worldwide and can result in serious economic losses each year. The PRRS epidemic situation in China has been very complicated since the unprecedented large-scale highly pathogenic PRRS (HP-PRRS) outbreaks in 2006. And now the HP-PRRS virus (HP-PRRSV) and classical North American type PRRSV strains have coexisted in China. Rapid differential detection of the two strains of PRRSV is very important for effective PRRS control. The real-time RT-PCR for simultaneous detection and differentiation of HP-PRRSV and PRRSV by using both SYBR Green and TaqMan probes was developed and validated. Both assays can be used for rapid detection and strain-specific identification of HP-PRRSV and PRRSV. However, the TaqMan probe method had the highest detection rate whereas the conventional RT-PCR was the lowest. The real-time RT-PCR developed based on SYBR Green and TaqMan probe could be used for simultaneous detection and differentiation of HP-PRRSV and PRRSV in China, which will benefit much the PRRS control and research.